MENGUAK PERSEPSI ETIKA MAHASISWA AKUNTANSI - Santi Novita (EKUITAS (Jurnal Ekonomi dan Keuangan), 2013)
The aims of this study was to determine whether there were ethical perception differences among students based on academic major, gender, and religiosity. It explored whether there was a perception gap between accounting students and non-accounting students, between male and female students, and between religious and non-religious students. The survey was conducted using questionnaire of 216 students to explore the ethical perception. It used five moral constructs: justice, relativism, egoism, utilitarianism, and deontology. At significant level of 5% with the independent sample t-tests, it was found that were different perception in justice, relativism, and deontology contracts between accounting and non-accounting students.  It displayed that in most of construct accept deontological, the accounting students had higher ethical values compared to non-accounting students.  The second result displayed that female students showing higher ethical perception toward their male students, and finally it was not displayed that there was different ethical perception between religious and non-religious students.